STUDIES ON In-vitro EVALUATION OF ANTIMICROBIAL ACTIVITY OF SILKWORM COCOON EXTRACTS - DEEPALI, .; SHARMA, MEENAKSHI; KUMAR, ANEESH; KUMAR, AMIT; BHATIA, VIKESH KUMAR; KUMARI, PRIYANKA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
Silk from the domesticated Bombyx mori cocoons is composed of adhesive glue (sericin) and fiber (fibroins) proteins which provide a physical barrier to protect pupa. The recovery and reuse of sericin not only minimizes environmental issues but also has high scientific and commercial value. The antimicrobial properties of sericin allow its application for drug delivery and cosmetics. The aim of the present study was to elucidate the antimicrobial efficacy persisted in the cocoons of Bombyx mori. The silkworm cocoon shell extracts were prepared, and their in vitro antimicrobial susceptibility testing was performed using disc diffusion method against Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus and Klebsiella pneumoniae. The cocoon shell extracts demonstrated significant antimicrobial activity. It was observed that all the bacterial strains were resistant against cepodoxime. These results unwrap the opportunity to develop a natural antibiotic based on sericin that may be used for the treatment of drug resistant bacteria. However further studies are still required to demonstrate the other beneficial effects of sericin.